24.8k views
0 votes
Please help i dont understand it

Please help i dont understand it-example-1
Please help i dont understand it-example-1
Please help i dont understand it-example-2
User Alecswan
by
6.3k points

1 Answer

4 votes

Answer:

Question 1: True

Question 2: True

Question 3: False

Question 4: True

Question 5 True

Explanation:

You have to replace the variables 'x' and 'y' by the given value inside the pair of each question and see if the inequalities are verified or not.

Question 1:

Pair is (3,-2), so x = 3 and y = -2

If you enter these in the provided inequalities, do they verify them (once you changed the values of x and y, is the inequality true or not)?

We'll verify the first inequality...

y ≤ x - 3 becomes -2 ≤ 3 - 3 becomes -2 ≤ 0

We replaced the variables x and y by the values given in the question, and made the calculations to simplify the expression.

Now, is -2 smaller or equal to 0? yes.

Let's verify the second inequality of question 1

y ≥ -x -2 becomes -2 ≥ -(3) -2 becomes -2 ≥ -5

Is -2 greater or equal to -5? Yes.

Since both inequalities are verified (are true), the answer to the question 1 is TRUE.

Question 2

Pair is (1,4), so x = 1 and y = 4

We'll verify the first inequality...

y > -3x + 3 becomes 4 > -3(1) + 3 becomes 4 > -3 + 3 becomes 4 > 0

That is true.

We'll verify the second inequality...

y > x + 2 becomes 4 > 1 + 2 becomes 4 > 3

Again this is true.

Since BOTH inequalities are true, the answer to the question 2 is TRUE.

Question 3:

Pair is (0,-2), so x = 0 and y = -2

We'll verify the first inequality...

y ≤ 3x - 6 becomes -2 ≤ 3(0) - 6 becomes -2 ≤-6

Is -2 less or equal to -6? No of course.

Since one is not true, the answer to the question 3 is FALSE.

Question 4:

Pair is (0,3), so x = 0 and y = 3

We'll verify the first inequality...

2x - y < 4 becomes 2(0) - 3 < 4 becomes -3 < 4

That is true.

Let's verify the second one:

x + y > -1 becomes 0 + 3 > -1 becomes 3 > -1

Which is also true. so the answer to the question 4 is TRUE.

Question 5:

Pair is (-3,0), so x = -3 and y = 0

We'll verify the first inequality...

y > 2x - 3 becomes 0 > 2(-3) - 3 becomes 0 > -6 -3 becomes 0 > -9

which is true.

the second one now...

y < -x + 6 becomes 0 < -(-3) + 6 becomes 0 < 9

Which is also true. so the answer to the question 5 is TRUE.

User Eugenn
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.